Immunologic evaluation of 10 different adjuvants for use in vaccines for chickens against highly pathogenic avian influenza virus. Issue 26 (8th June 2017) - Lone, Nazir Ahmed; Spackman, Erica; Kapczynski, Darrell
Highlights: Vaccination with adjuvanted vaccines is used in regions where avian influenza is endemic. Ten adjuvants were compared and oil based adjuvants performed the best in chickens. Beta-propiolactone and formalin inactivated vaccines produced similar protection. Abstract: Avian influenza viruses (AIV) are a threat to poultry production worldwide. Vaccination is utilized as a component of control programs for both high pathogenicity (HP) and low pathogenicity (LP) AIV. Over 95% of all AIV vaccine used in poultry are inactivated, adjuvanted products. To identify the best formulations for chickens, vaccines were prepared with beta-propiolactone (BPL) inactivated A/British Columbia/314514-1/2004 H7N3 LP AIV using ten commercially available or experimental adjuvants. Each vaccine formulation was evaluated for immunogenicity in chickens. Challenge studies with an antigenically homologous strain of HPAIV were conducted to compare protection against mortality and measure reductions in virus levels in oral swabs. The four best adjuvants from the studies with BPL inactivated antigen were selected and tested identically, but with vaccines prepared from formalin inactivated virus. Mineral and vegetable oil based adjuvants generally induced the highest antibody titers with 100% seroconversion by 3 weeks post vaccination. Chitosan induced positive antibody titers in 100% of the chickens, but the titers were significantly lower than those of most of the oil based adjuvants. Antibody levels from calcium phosphate and alginate adjuvanted groups were similar to those of non-adjuvanted virus. All groups that received adjuvanted vaccines induced similar levels of protection against mortality (0–20%) except the groups vaccinated with calcium phosphate adjuvanted vaccines, where mortality was similar (70%) to groups that received non-adjuvanted inactivated virus or no vaccine (60–100% mortality). Virus shedding in oral swabs was variable among the treatment groups. Formalin inactivated vaccine induced similar antibody titers and protection against challenge compared to BPL inactivated vaccine groups. These studies support the use of oil adjuvanted vaccines for use in the poultry industry for control for AIV.